INHIBITION ACTIVITY OF BELIMBING WULUH(Averrhoa bilimbi linn) LEAF EXTRACT TO Streptococcus mutans ON ACRYLIC PLATE - Debby Saputera; Irma Zufira; Lia Yulia Budiarti (FKG Unlam, 2018)
Background: The leaf of Averrhoa bilimbi contains flavonoids and tannins as antibacterial agent against Streptococcus mutans. The extract of Averrhoa bilimbi leaf can be used as a natural alternative ingredients of denture cleanser. Purpose: The main purpose of this research is to know the different antibacterial activities of Averrhoa bilimbi leaf extract 6.25%, 12.5%, 25%, 50%, and 100% against Streptococcus mutans on acrylic plate. Methods: The method of this research was true experimental with posttest-only with control group design that consisted of Averrhoa bilimbi leaf extract in 6.25%, 12.5%, 25%, 50%, 100% and chlorhexidine gluconate 0.2%. The antibacterial testing method was using diffusion method. The measurement parameter was the amount of inhibition zone formed in the test medium. The data analysis was using Kruskall-Wallis test which resulted in p=0.000 (p<0.05). The result showed that there were differences in the inhibitory activity between each group. The test then continued with Mann Whitney test that results in p=0.009 (p<0.05) which showed meaningful differences between each group. Results: The smallest inhibitory zone of 6.25% was 10.08 mm, the biggest inhibitory zone of 100% was 23.07 mm, and the inhibitory zone of chlorhexidine gluconate in 0.2% was 25.05 mm. The lower extract concentration inhibitory zone were smaller than the high extract concentration. There was significant increase in inhibitory activity of Averrhoa bilimbi leaf extracts cause by the flavonoids and tannins content as antibacterial. Conclusion: It can be concluded that there are differences in the inhibitory activity of Averrhoa bilimbi leaf extract and chlorhexidine gluconate 0.2%.